Duckweed (Lemnaceae): Its Molecular Taxonomy - Bog, Manuela; Appenroth, Klaus-J.; Sree, K. Sowjanya (Frontiers in Sustainable Food Systems, 2019)
Duckweeds include the world’s smallest and fastest growing flowering plants that have the capacity to produce huge biomass with a broad range of potential applications like production of feed and food, biofuel and biogas. In order to achieve optimal and sustainable commercial system, it is necessary that suitable species and clones of duckweeds be identified and selected based on appropriate strategies. However, a high degree of reduction in their structural complexity poses serious problems in identification of closely related species of duckweeds, on a morphological basis. Use of molecular taxonomic tools is the present solution. The state of the art of molecular taxonomy of all the five genera of duckweeds (Spirodela, Landoltia, Lemna, Wolffiella and Wolffia) is based mainly on the techniques of fingerprinting by amplified fragment length polymorphism (AFLP) and barcoding using sequences of plastidic DNA fragments. After more than 15 years of molecular taxonomic investigations, a certain viewpoint is now available demonstrating all five genera to be monophyletic. Also, the phenetic analyses had made huge progress in delineating the currently defined 36 species of duckweeds, although, all species cannot yet be defined with confidence. Wolffiella has turned out to be the most complicated genus as only 6 to 7 species out of the 10 can be reliably delineated. Further progress in the phylogenetic and phenetic analyses requires more advanced methods like next generation and/or whole genome sequencing. First results using the method genotyping-by-sequencing in the genus Lemna (in combination with metabolomic profiling by matrix-assisted laser desorption ionization time-of-flight mass-spectrometry (MALDI-TOF-MS) as well as AFLP and barcoding by plastidic sequences) are more promising: The species Lemna valdiviana and Lemna yungensis were united to one species, Lemna valdiviana. This reduced the total number of Lemnaceae species to 36.